PERBANDINGAN HASIL BELAJAR MODEL PEMBELAJARAN TPS DAN GI MEMPERHATIKAN MOTIVASI BELAJAR - Khurin Ain; I Komang Winatha; Tedi Rusman (FKIP Unila, 2019)
This study aims to compare the results of economic learning between students taught by using TPS and GI learning models by paying attention to learning motivation. The method used is a quasi-experimental method. The study population was eleventh grade students of MA Daarul Ma'arif Natar in the even semester academic year 2018/2019. Sampling is done using saturated samples. Hypothesis testing uses two-way variance analysis and two independent T-test samples. The results of the study show: there are differences in economic learning outcomes with TPS and GI learning models. The average economic learning outcomes of students who are learning using the TPS cooperative learning model are higher than the GI learning model in students who have high learning motivation and GI is higher than TPS in students who have low learning motivation. There is an interaction between the learning model and motivation to learn on economic subjects.Penelitian ini bertujuan untuk mengetahui perbandingan hasil belajar ekonomi antara siswa yang diajar dengan menggunakan model pembelajaranTPS dan GI dengan memperhatikan motivasi belajar. Metode yang digunakan adalah metode eksperimen semu. Populasi penelitian adalah siswa kelas XI MA Daarul Ma’arif Natar semester genap tahun pelajaran 2018/2019. Pengambilan sampel dilakukan dengan menggunakan sampel jenuh. Pengujian hipotesis menggunakan analisis varians dua jalan dan uji T-test dua sampel independen Hasil penelitian menunjukkan: Terdapat perbedaan hasil belajar ekonomi dengan model pembelajaran TPS dan GI. Rata-rata hasil belajar ekonomi siswa yang pembelajarannnya menggunakan model pembelajaran kooperatif TPS) lebih tinggi dibandingkan model pembelajaran GI pada siswa yang memiliki motivasi belajar tinggidan GI lebih tinggi dibandingkan TPS pada siswa yang memiliki motivasi belajar rendah. Ada interaksi antara model pembelajaran dengan motivasi belajar pada mata pelajaran ekonomi. Kata Kunci :Ekonomi, group investigation, hasil Belajar, numbe, dan think pair and share.